2015
DOI: 10.1021/acs.biomac.5b01260
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Biopolymer Degradation by Taylor Dispersion Analysis

Abstract: This work aims at demonstrating the interest of modern Taylor dispersion analysis (TDA), performed in narrow internal diameter capillary, for monitoring biopolymer degradations. Hydrolytic and enzymatic degradations of dendrigraft poly-l-lysine taken as model compounds have been performed and monitored by TDA at different degradation times. Different approaches for the data processing of the taylorgrams are compared, including simple integration of the taylorgram, curve fitting with a finite number of Gaussian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…Although TDA is not new, the phenomenon and the related method were described already in the 1950s (Aris 1956;Taylor 1953Taylor , 1954, it has been recently reintroduced to measuring the size of NPs (Cipelletti et al 2014;Biron et al 2014;Cipelletti et al 2015;Biron et al 2015;d'Orlye et al 2008;Varenne et al 2008;Hawe et al 2011;Hulse et al 2011;Oukacine et al 2015;Morel et al 2015;Pyell et al 2015;Jalil et al 2015;Wuelfing et al 1999;Templeton et al 1999). Traditionally, TDA was applied to observe chemical reactions (Chamieh et al 2015;Biron et al 2015;Cotett 2010) and characterize small molecules, proteins, and macro molecules (Bello et al 1994;Rezzonico et al 1994;Belongia and Baygents 1997;Chamieh et al 2012;Oukacine et al 2012;Cipelletti et al 2014, Biron et al 2014Cipelletti et al 2015;Biron et al 2015;Cotett 2010;d'Orlye et al 2008;Varenne et al 2008, Goodall 2010Hawe et al 2011;Hulse et al 2011;Hulse and Forbes 2011;Oukacine et al 2015;Morel et al 2015;Pyell et al 2015;Jalil et al 2015;Saux and Cottet 2008;…”
Section: Introductionmentioning
confidence: 99%
“…Although TDA is not new, the phenomenon and the related method were described already in the 1950s (Aris 1956;Taylor 1953Taylor , 1954, it has been recently reintroduced to measuring the size of NPs (Cipelletti et al 2014;Biron et al 2014;Cipelletti et al 2015;Biron et al 2015;d'Orlye et al 2008;Varenne et al 2008;Hawe et al 2011;Hulse et al 2011;Oukacine et al 2015;Morel et al 2015;Pyell et al 2015;Jalil et al 2015;Wuelfing et al 1999;Templeton et al 1999). Traditionally, TDA was applied to observe chemical reactions (Chamieh et al 2015;Biron et al 2015;Cotett 2010) and characterize small molecules, proteins, and macro molecules (Bello et al 1994;Rezzonico et al 1994;Belongia and Baygents 1997;Chamieh et al 2012;Oukacine et al 2012;Cipelletti et al 2014, Biron et al 2014Cipelletti et al 2015;Biron et al 2015;Cotett 2010;d'Orlye et al 2008;Varenne et al 2008, Goodall 2010Hawe et al 2011;Hulse et al 2011;Hulse and Forbes 2011;Oukacine et al 2015;Morel et al 2015;Pyell et al 2015;Jalil et al 2015;Saux and Cottet 2008;…”
Section: Introductionmentioning
confidence: 99%
“…Several effects, such as the polydispersity of the sample itself, wall interactions, or instrumental errors, may cause slight differences in the signal symmetry, however seem not to have a significant influence in the data analysis in our case. Additional literature on the analysis of nanoparticles with TDA can be found from Cipeletti et al [16,17], Belongia and Baygents [18], and Balog et al [32] Results for the sizes obtained by the three instruments are shown in Table 1. The numbers from the TEM correspond to the mean size of the counted particles followed by the standard deviation.…”
Section: Da Urban Et Almentioning
confidence: 99%
“…In other words, larger NPs will be dispersed more strongly by convection than smaller ones, and by detecting the band broadening of these concentration fronts, and obtaining so-called Taylorgrams of the NPs, one can determine hydrodynamic sizes by fitting the Taylorgram against a Gaussian function [13][14][15]. In the past, TDA has mainly been used to observe chemical reactions [16,17], or to determine the diffusion coefficient of small molecules, proteins, and polymers [10,11,[18][19][20]. With the increasing interest in nanomaterials, some work has been done in the past [9,13,15,18,[21][22][23][24] to investigate whether TDA can be used for NP characterization.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it was demonstrated that DGLs are readily soluble in water at least up to 60 gL À1 in water, [12] are stable under sterilization conditions, [28] and are partially degradable under the action of endogenous peptidases. [29] In addition, these biomacromolecules are non-immunogenic [30] and carry low cytotoxicity (i.e., IC50 values on Hep2 cellso f1 6.8, 13.2, and 13.9 mgmL À1 from second-to fourth-generation DGL, respectively), [31] in comparison with other polycationic polymers (e.g.,a bout 90 %v iability for DGL G3 versusl ess than 50 %v iability for hyperbranched PEI at as ame concentration of 12.5 mgmL À1 on HeLa cells). [32] As aresult, DGLs have already attracted the interest of multiple researchg roups during the last fivey ears, and found numerous applications in the biomedical field, in which the ability of the arborescent polymers to display multiple functionalities has been exploited.…”
Section: Biology Biocompatibilitymentioning
confidence: 99%